2023
DOI: 10.4236/ojgas.2023.131002
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Platelet Count with Grading of Esophageal Varices in Cirrhotic Patients

Abstract: Background/Aims: Cirrhosis represents a late stage of progressive hepatic fibrosis and is generally considered to be irreversible in its advanced stages. Esophageal varix is a complication of liver cirrhosis and is the consequence of portal hypertension. The aim of this study was to determine the correlation between the severity of thrombocytopenia and the presenting of esophageal varices (EVs) in cirrhotic patient. Patients and Methods: This study was a retrospective, descriptive, analytic and monocentric stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…The mean age of patients diagnosed with liver cirrhosis, irrespective of its root cause or the manifestation of EVs, was calculated to be 51.06 ± 11.09 years. This finding is in congruence with previous studies conducted by Abbasi et al and Uong et al, which reported similar age distribution among their patient cohorts [11,16].…”
Section: Discussionsupporting
confidence: 93%
“…The mean age of patients diagnosed with liver cirrhosis, irrespective of its root cause or the manifestation of EVs, was calculated to be 51.06 ± 11.09 years. This finding is in congruence with previous studies conducted by Abbasi et al and Uong et al, which reported similar age distribution among their patient cohorts [11,16].…”
Section: Discussionsupporting
confidence: 93%